Determinan Niat Pembelian Produk Skincare Ramah Lingkungan di Indonesia: Pendekatan Theory of Planned Behavior yang Diperluas - Sumbung, Kezia Rama Lisupindan; Pratomo, Luki Adiati (Jurnal EMT KITA, 2026)
This study aims to analyze the factors influencing consumer's green purchase intention towards eco-friendly skincare products in Indonesia using the Theory of Planned Behavior (TPB) framework. The research method used was a quantitative approach with a purposive sampling technique through the distribution of questionnaires to 260 respondents. Data were analyzed using SEM through the AMOS program. The results showed that attitude toward green products and subjective norms had a positive and significant effect on green purchase intention. Meanwhile, perceived behavioral control did not have a significant effect on purchase intention towards eco-friendly skincare products. In addition, environmental knowledge did not directly influence attitude toward green products, but had a positive and significant effect on environmental sensitivity. Furthermore, environmental sensitivity and eco-labels were proven to have a positive and significant effect in shaping consumer attitudes towards eco-friendly skincare products. In conclusion, this study provides practical implications and strategic decision-making for eco-friendly skincare companies to optimize environmental education programs, product availability, and strengthen positive consumer attitudes through marketing communications that emphasize environmental benefits, ingredient safety, and product ethical value.